Dental arch dimensions in primary dentition of children aged three to five years in Chennai and Hyderabad - Prabhakaran S; Sriram C; Muthu M; Rao Chandrasekhar; Sivakumar N (Wolters Kluwer Medknow Publications, 2006)
OBJECTIVE : The purpose of this study was to assess the arch dimensions in primary dentition of 3-5 years old children in Chennai and Hyderabad. As no primary to the mixed dentition and determining the existence of sexual dimorphism. METHODS : Children were selected fro various schools of both Chennai and Hyderabad, with complte set of primary dentition. Study casts were made and measurements of arch dimensions were made using digital sliding calipers. The data obtained was subjected to statistical analysis. RESULTS : The mean values and standard deviations of the various arch dimensions are given in the tables. CONCLUSION : Generally boys exhibited a greater arch dimensions than girls in both groups. Some of the dimensions showed a statistically significant mean values.